Caucasian lean subjects with non-alcoholic fatty liver disease share long-term prognosis of non-lean: time for reappraisal of BMI-driven approach?. Issue 2 (4th February 2021) - Younes, Ramy; Govaere, Olivier; Petta, Salvatore; Miele, Luca; Tiniakos, Dina; Burt, Alastair; David, Ezio; Vecchio, Fabio Maria; Maggioni, Marco; Cabibi, Daniela; McLeod, Duncan; Pareja, Maria Jesus; et al.
Abstract : Objective: The full phenotypic expression of non-alcoholic fatty liver disease (NAFLD) in lean subjects is incompletely characterised. We aimed to investigate prevalence, characteristics and long-term prognosis of Caucasian lean subjects with NAFLD. Design: The study cohort comprises 1339 biopsy-proven NAFLD subjects from four countries (Italy, UK, Spain and Australia), stratified into lean and non-lean (body mass index (BMI) </≥25 kg/m 2 ). Liver/non-liver-related events and survival free of transplantation were recorded during the follow-up, compared by log-rank testing and reported by adjusted HR. Results: Lean patients represented 14.4% of the cohort and were predominantly of Italian origin (89%). They had less severe histological disease (lean vs non-lean: non-alcoholic steatohepatitis 54.1% vs 71.2% p<0.001; advanced fibrosis 10.1% vs 25.2% p<0.001), lower prevalence of diabetes (9.2% vs 31.4%, p<0.001), but no significant differences in the prevalence of the PNPLA3 I148M variant (p=0.57). During a median follow-up of 94 months (>10 483 person-years), 4.7% of lean vs 7.7% of non-lean patients reported liver-related events (p=0.37). No difference in survival was observed compared with non-lean NAFLD (p=0.069). Conclusions: Caucasian lean subjects with NAFLD may progress to advanced liver disease, develop metabolic comorbidities and experience cardiovascular disease (CVD) as well as liver-related mortality, independent of longitudinal progression to obesity and PNPLA3 genotype. These patients represent one end of a wide spectrum of phenotypic expression of NAFLD where the disease manifests at lower overall BMI thresholds. Lay summary: NAFLD may affect and progress in both obese and lean individuals. Lean subjects are predominantly males, have a younger age at diagnosis and are more prevalent in some geographic areas. During the follow-up, lean subjects can develop hepatic and extrahepatic disease, including metabolic comorbidities, in the absence of weight gain. These patients represent one end of a wide spectrum of phenotypic expression of NAFLD.